Mitigation of oscillatory instability in turbulent reactive flows: A novel approach using complex networks. (27th November 2019) - Krishnan, Abin; Manikandan, R.; Midhun, P. R.; Reeja, K. V.; Unni, V. R.; Sujith, R. I.; Marwan, Norbert; Kurths, Jürgen
Abstract: We present a novel and an efficient way to mitigate oscillatory instability in turbulent reactive flows. First, we construct weighted spatial correlation networks from the velocity field obtained from high-speed particle image velocimetry. Using network measures, we identify the optimal location for implementing passive control strategies. By injecting micro-jets at this optimal location, we are able to reduce the amplitude of the pressure oscillations to a value comparable to what is observed during the state of stable operation. This approach opens up new avenues to control oscillatory instabilities in turbulent flows.